Increasing the Students’ Speaking Ability through Role-Playing with Slovin’s Formula Sample Size - Anugraheni, Tiara Djati; Izzah, Lidiyatul; Hadi, Muhamad Sofian (Jurnal Studi Guru dan Pembelajaran, 2023)
The ability to communicate is required at this time because it allows for effective communication of ideas, information, and other concepts. To enhance speaking skills, one must use the appropriate media, including flashcard learning media employing the role-playing method. The purpose of this study is to determine the extent to which the Role-Playing Card method with Slovin’s Formula as the sample size can increase students' speaking abilities. The purpose of this experimental study is to determine whether the use of Role-Playing Cards can assist students in developing their speaking abilities. This investigation employed a pre-experimental design. This study involved 42 eighth-grade students from SMPN 19 Kota Tangerang Selatan. Information gathered from the pre- and post-tests The results of the analysis indicate that the t-test value (12,195) is significantly greater than the t-table (23,190). This shows that the null hypothesis (H0) or negative hypothesis, namely that role-playing card methods cannot increase students' speaking ability, cannot be accepted, and the alternative hypothesis (H1) or positive hypothesis, namely that role-playing card methods can increase students' speaking ability, must be accepted. This research concludes, based on the results of t-test calculations, that the role-playing card method is an effective medium for helping students hone their speaking skills